Aegidius Strauch Wittebergensis S.S. Theologiae Doctor Prof. P. Pastor Et Rector Gymnasii Gedanensis. - Beckmann, Johann Christoph (1641-1717); Stech, Andreas (1635-1697) (1680)
Przedstawia portret w popiersiu teologa i pastora Aegidiusa Straucha (1632-1682).